Increased Motivation and Student Outcomes Through Problem Based Learning (PBL) in Mathematics Learning - Arofiq Arofiq (IJECA (International Journal of Education and Curriculum Application), 2019)
The material in mathematics learning is considered boring and monotonous. This proves that there are students who have not been able to reach the minimum success rate. Therefore, the purpose of this research is to know the increased motivation and learning outcomes of students through Problem Based Learning (PBL). This research is a class action research implemented over two cycles. Each cycle consists of planning, implementation, action, observation, and reflection phases. The research instruments used are observation sheets, tests, and polls. Data collection techniques using interviews and documentation. While data analysis uses qualitative and quantitative descriptive analysis techniques. The results of the action showed an increase in motivation and student learning outcomes through the implementation of a problem based learning (PBL).  The student's learning motivation increased 75% well-endowed in cycle I increased to 87.5% which was very well-endowed in cycle II. While the results of learning in pre-action, the learners showed an average of 78.20 increased to 81.05 in cycle I, and increased to 88.50 in cycle II. The conclusion of this study is problem based learning (PBL) can significantly increase the motivation and learning outcomes of students